The Influence of Measuring Location on Volume Estimation by Shadow Casting Method - T. Suesut; Siwakorn Sukprasertchai (My University, 2024)
Non-contact inspection has dominated various industries for many years, particularly in the field of food and agricultural processes. Volume estimation can be achieved by volumetric imagery or 3D reconstruction. The casting of shadows or shape by shading is an active technique that can be utilized to generate volumetric imagery. By evaluating the length of shadows, the object height data can be achieved, and the transformation of image coordinates to world coordinates is facilitated by means of homography transformation. The width, length, and height of object edges along the entirety of its length are employed to reconstruct virtual slices. The integration of these virtual slices enables the estimation of the object's volume. This research studied the variation of the measuring locations, three different diameters spherical balls 38mm, 50mm, and 80mm are used as test materials. The percentage of errors in volume obtained from all sections by shadow casting were compared to computation volume of sphere formula is approximately -1.6 %, -1.13 %, and - 6.60%, respectively, depending on the size of the object. Furthermore, a visualization-based analysis is presented which has no significant difference. From this studied, it can be concluded that this method is valuable in estimating the volume of axially symmetrical objects.
Keywords: Metallurgy and Material Forming; Industrial Vision Systems and Defect Detection; Metallurgical Processes and Thermodynamics